The Role of Dopamine in the Stimulant Characteristics of Novel Psychoactive Substances (NPS)—Neurobiological and Computational Assessment Using the Case of Desoxypipradrol (2-DPMP) - Loi, Barbara; Sahai, Michelle A.; De Luca, Maria Antonietta; Shiref, Hana; Opacka-Juffry, Jolanta (Frontiers in Pharmacology, 2020)
Stimulant drugs, including novel psychoactive substances (NPS, formerly ‘legal highs’) have addictive potential which their users may not realise. Stimulants increase extracellular dopamine levels in the brain, including the reward and addiction pathways, through interacting with dopamine transporter (DAT). This work aimed to assess the molecular and atomistic mechanisms of stimulant NPS actions at DAT, which translate into biological outcomes such as dopamine release in the brain’s reward pathway. We applied combined in vitro, in vivo and in silico methods and selected 2-diphenylmethylpiperidine (2-DPMP) as an example of stimulant NPS for this study. We measured in vitro binding of 2-DPMP to rat striatum and accumbens DAT by means of quantitative autoradiography with a selective DAT-radioligand [125I]RTI-121. We evaluated the effects of intravenously administered 2-DPMP on extracellular dopamine in the accumbens-shell and striatum using in vivo microdialysis in freely moving rats. We used dynamic modelling to investigate the interactions of 2-DPMP within DAT, in comparison with cocaine and amphetamine. 2-DPMP potently displaced the radioligand in the accumbens and striatum showing dose-dependence from 0.3 to 30μM. IC50 values were: 5.65x10-7M for accumbens shell and 6.21x10-7M for dorsal striatum. Dose-dependent responses were also observed in accumbens-shell and striatum in vivo, with significant increases in extracellular dopamine levels. Molecular dynamics simulations identified contrasting conformational changes of DAT for inhibitors (cocaine) and releasers (amphetamine). 2-DPMP led to molecular atomistic rearrangements towards an outward-facing DAT conformation that suggested a cocaine-type effect. The present combination of molecular modelling with experimental neurobiological procedures allows for extensive characterisation of the mechanisms of drug actions at DAT as the main molecular target of stimulants, and provides an insight into the role of dopamine in the molecular atomistic and neurobiological mechanisms of brain responses to stimulant NPS that have addictive potential. Such knowledge reveals the risk of addiction related to NPS use. The research presented here can be adapted for other psychostimulants that act at their membrane protein targets.